2021
DOI: 10.1002/app.50608
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy‐functional thermoplastic copolymers and their incorporation into a thermosetting resin

Abstract: The customization of polymer networks can be made possible via dual-functional monomers, molecules characterized by two different reactive substituents that allow for versatile methods of polymerization. The dual-functional, epoxymethacrylate monomers, glycidyl methacrylate (GMA), and vanillyl alcohol epoxy-methacrylate (VAEM), were polymerized with methyl methacrylate (MMA) via reversible addition-fragmentation chain transfer (RAFT) polymerization to form low molecular weight (~10-20 kDa) epoxy-functional the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…This suggests that the influence of the hardener on the Poisson’s ratio of the polymerized samples is negligible. In an experimental study, Sweet and Stanzione reported a similar value, 0.35, as the Poisson’s ratio of the dual-cured GMA/epoxy system …”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…This suggests that the influence of the hardener on the Poisson’s ratio of the polymerized samples is negligible. In an experimental study, Sweet and Stanzione reported a similar value, 0.35, as the Poisson’s ratio of the dual-cured GMA/epoxy system …”
Section: Resultsmentioning
confidence: 74%
“…In an experimental study, Sweet and Stanzione reported a similar value, 0.35, as the Poisson's ratio of the dual-cured GMA/epoxy system. 41 Future Directions. In future, this methodology will be translated to investigate carbon fiber reinforced polymer composites (CFRPs).…”
Section: T H Imentioning
confidence: 99%
“…Epoxy-based materials are one class of the most versatile polymers extensively applied in coating, microelectronic packing, and adhesive fields, due to their outstanding mechanical properties and good chemical stability, as well as easy processing, low cost, and commercial abundance. It is quite well-known that thermosetting epoxy materials can be achieved by curing epoxides with hardeners such as polyfunctional amines, anhydrides, and phenolic esters. The thermosetting epoxy resin may become brittle and quite fragile to crack growth and propagation after curing due to their high cross-link density, which hugely limits their application in high-tech fields. Alternatively, high-molecular-weight linear epoxy resins, so-called thermoplastic phenoxy resins, possess high rigidity, ductility, toughness, and creep resistance as compared to the brittle thermosetting ones, and can be ideal alternate and toughening agents to improve the toughness and mechanical properties. …”
Section: Introductionmentioning
confidence: 99%
“…It's known that the resin toughness has a direct and important impact on the interface and macroscopic mechanical properties of resin matrix composites. [22][23][24][25] However, E-beam curable resin has low toughness, showing poor ability to inhibit crack propagation and is easy to crack under the action of external load, while the cracks extending from the matrix to the interface or the rapid expansion of tiny cracks originally existing at the interface can easily cause the integral de-bonding of the interface and directly lead to the failure of the component destroy. The strength and toughness of the initial electron beam curing resin are even lower than the minimum standard of thermal curing resin.…”
Section: Introductionmentioning
confidence: 99%